5h+6(2h+10)=10

Simple and best practice solution for 5h+6(2h+10)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5h+6(2h+10)=10 equation:


Simplifying
5h + 6(2h + 10) = 10

Reorder the terms:
5h + 6(10 + 2h) = 10
5h + (10 * 6 + 2h * 6) = 10
5h + (60 + 12h) = 10

Reorder the terms:
60 + 5h + 12h = 10

Combine like terms: 5h + 12h = 17h
60 + 17h = 10

Solving
60 + 17h = 10

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + 17h = 10 + -60

Combine like terms: 60 + -60 = 0
0 + 17h = 10 + -60
17h = 10 + -60

Combine like terms: 10 + -60 = -50
17h = -50

Divide each side by '17'.
h = -2.941176471

Simplifying
h = -2.941176471

See similar equations:

| 3x-2(5x-y)-(4y+x)= | | w^2(w-3)=350 | | 5x-22=26+x | | Y^2-2y= | | 3.4+z=-7 | | -6th-7=17 | | 1/3x-1/7=8 | | x^2+38x+361=36 | | 5xy-3y+10x-6= | | x-2(x+1)=5+9 | | 15/2x+4=-2 | | 12t=16 | | 2x^2+xy-y^2=2 | | (2c)(3c)=6c | | 16340/40 | | 8*3=7x | | 15/2+4=-2 | | 36-45x+2=42x-49 | | k/3-19 | | (2x+30)=4x | | 11x-1=7x+10 | | -5(z+1)-(4z-6)=-10z | | 2n^2-n-120=0 | | 3x-8=158 | | 3(y-0.3)=19.4-y | | 2.4=t-/4.5 | | 6/3p-1=10 | | x^2+38x+361=0 | | 4+10=7A | | 5(5x+6)= | | sqrtx=1/4 | | 0=s^2+6s+10 |

Equations solver categories